Optimizing Time and Cost of Column Formwork Work in Multi-Story Buildings Through a Zoning System (Case Study: Multimedia Nusantara School Project) - Dwi Novi Setiawati; Siti Asyiah; Rifky Ujianto; Mush'ab Abdu Asy Syahid; Ahmad Fauzan Ardiansyah (JURUSAN TEKNIK SIPIL, 2026)
Construction activities generally use concrete as the main material, one of which is in reinforced concrete columns that function to withstand vertical loads and distribute them to the lower parts of the structure. In the Multimedia Nusantara School project, which was carried out independently, formwork work often faced the challenge of completing the project quickly and at a low cost. Therefore, this study was conducted to examine effective and efficient work methods that reduce costs while maintaining quality, namely through the application of a zoning system. In this study, the work area was divided into two scenarios, namely 1 work zone and 2 work zones, to see the differences in their effectiveness. In addition, the types of column formwork used consisted of two types of materials, namely fiberglass formwork and conventional formwork. The main objective of this study was to determine the optimal work zone division model and to analyze the relationship and role of the zoning system in the time and cost efficiency of column formwork work. This research method was carried out using a qualitative descriptive approach using project planning data. The analysis was carried out using Microsoft Excel software to analyze the implementation time and cost estimates. The results of the study indicate that the application of two zones is the most optimal model for column formwork work. The application of the zoning system directly affects the relationship between time efficiency and cost. The shorter the cycle time applied, the higher the implementation cost tends to be due to more intensive use of resources. Based on the analysis results, the model with 2 zones and a 7 day cycle is the most efficient option, as it can speed up completion time to 44 days with a total cost of Rp294,899,522.